Leadership Style on Job Satisfaction of Madrasah Aliyah Educational Personnel in The Ministry of Religion in Jambi Province - Ikhtiati Ikhtiati; Mukhtar Latif; Risnita Risnita (International Journal of Islamic Thought and Humanities, 2023)
This research aims to describe and analyze the magnitude of the direct and indirect influence between the variables of leadership style, work commitment and work motivation on job satisfaction of State Madrasah Aliyah education staff within the Ministry of Religion of Jambi province. The research uses a quantitative approach by collecting data through questionnaires with a Likert scale which is analyzed using path analysis. The research results show There is an influence between leadership style (X1), work commitment (X2) and work motivation (X3) which influence job satisfaction (X4). The results of this research are seen from the results of data prerequisite tests with research results on leadership style, work commitment, work motivation and job satisfaction having a normal and homogeneous distribution. With the results of the hypothesis test criteria Fcalculated (88.234) > F table (3.94), so that H 0 is rejected and H1 is accepted. So the calculation uses the path coefficient between leadership style (X1), work commitment (X2) and work motivation (X3) which influence job satisfaction (X4), the influence given is 0.852 which if expressed as a percentage becomes 85.2% which means H0 is rejected and H1 accepted with the remaining 0.148 or if the percentage is 14.8% influenced by other variables. The results of manual calculations get the same numbers as calculations using SPSS 25. In an effort to realize the ideal leadership style, namely using quality resources . School leaders must use resources wisely and not waste them in vain. In a work context, this means that both leaders and employees must focus on important tasks and prioritize time and energy to achieve relevant goals.